Assessment of radioactivity and heavy metal contents in surface water samples from Van Lake, Turkey - Kayakökü, Halime; Doğru, Mahmut (Springer Science and Business Media Deutschland GmbH, 2021)
The aim of this study was to determine the natural radioactivity levels of surface water samples obtained from Van Lake in spring and autumn seasons. For this purpose, the gross alpha and beta radioactivity levels of the samples were measured by using ultra-low level alpha/beta (?/?) counter device. In addition, ICP-OES device was used to determine whether there was heavy metal pollution in the lake or not. Multiple element analyses were performed for Zn, Fe, Mn, Ni, Cu, Cr, and Co in the samples. The results obtained were evaluated by considering the limit values given and the results reached in similar studies. In this study, it was seen that the average gross alpha and beta radioactivity values did not exceed the allowed limit values. It was also seen that the concentrations of heavy metals in water samples obtained did not exceed acceptable concentrations in water according to national and international standards except for Zn. © 2021, Saudi Society for Geosciences.
Keywords: Gross alpha; Gross beta; Heavy metal; Natural radioactivity; Van Lake; Water